Correction of Mild-to-Moderate Constricted Ear Abnormality Using Mustardé Suture, Cartilage Onlay Graft, and Transposition Flap: A Case Report - Nam, Ha Jong; Wee, Syeo Young (Archives of Plastic Surgery, 2023)
Constricted ear has a prevalence of 5.2 to 10% among ear abnormalities, and various surgical methods are suggested for treatment. We introduce a case of a constricted ear treated with a simple method using a novel concept cartilage graft and transposition flap, along with the well-known Mustardé suture, which is used for pediatric patients with mild to moderate constricted ears of Tanzer classification type IIA. A 10-year-old female patient visited the hospital complaining of an abnormality in the congenital right ear. Surgical approach was planned under the diagnosis of Tanzer classification type IIA constricted right ear. Posterior helix onlay graft and perichondrocutaneous transposition flap using excessive helical cartilage were performed along with the Mustardé suture. In the immediate postoperative period, ear contour was improved, and it was well-maintained without recurrence until 6 months' follow-up. In conclusion, the combination of Mustardé suture, and cartilage onlay graft and perichondrocutaneous transposition flap in the mild to moderate constricted ear would be a useful surgical option, producing aesthetically good results in a simple and effective method.
Keywords: ears prominent and constricted; external ear cartilage; surgical flaps